Allergic Contact Dermatitis of the Scalp Associated With Scalp Applied Products: A Systematic Review of Topical Allergens. Issue 4 (22nd July 2022) - Pham, Christine T.; Juhasz, Margit; Lin, Jessica; Hashemi, Kiana; Honari, Golara; Mesinkovska, Natasha Atanaskova
Abstract: Hair products are commonly used to maintain hair health or cosmesis. Products applied to the scalp and hair contain multiple active and inactive ingredients that can potentially cause irritant and/or allergic contact dermatitis. The objectives of this study were to identify and to discuss the most common allergens in scalp and hair applied products causing scalp allergic contact dermatitis (ACD). A PubMed search identified 99 studies, with 3185 patients and 31 categories of scalp products. Hair products reportedly associated with scalp ACD were hair dyes (41%), shampoos (28%), and conditioners (22%). The most commonly reported patch test–positive allergens were p -phenylenediamine (23%), nickel (15%), fragrance mix (13%), balsam of Peru (10%), cocamidopropyl betaine/3-dimethylaminopropylamine (7%), and methylchloroisothiazolinone/methylisothiazolinone (6%). Common symptoms and signs include eczematous lesions, pruritus, and a burning sensation. Medical practitioners should be aware of causative agents to provide appropriate patient education, counseling, and/or treatment.